2023
DOI: 10.1007/s00344-023-10966-5
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Effects of Calcium and Salicylic Acid on Fusarium graminearum-Infected Wheat Seedlings

Abstract: Fusarium graminearum is among the most virulent pathogens attacking wheat plants and significantly lowering its production globally. The present work aims to shed light on the interactions between two priming solutions, calcium (Ca) or salicylic acid (SA), and F. graminearum inoculation depending on the growth rate, physiological attributes, and molecular responses in wheat seedlings. In a pot experiment, F. graminearum-pre-inoculated or inoculum-free sandy soil was used to germinate wheat kernels after primin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 124 publications
0
1
0
Order By: Relevance
“…There are reports that the insect pest infestation leads to decrease in chlorophyll content (Murugesan and Kavitha, 2010 ; Singh et al, 2022 ). Many studies demonstrated that the concentration of chlorophyll in plants decrease with infection of pathogen (Akbar et al, 2023 ; Smith et al, 2023 ; Sobhy et al, 2023 ). The decreased chlorophyll content in leaves following fungal invasion may be attributed to the excessive loss of water owing to increased stomatal conductance (Baghbani et al, 2019 ) or to the overproduction of ROS as a protective barrier which further accelerate the breakdown of chlorophyll.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that the insect pest infestation leads to decrease in chlorophyll content (Murugesan and Kavitha, 2010 ; Singh et al, 2022 ). Many studies demonstrated that the concentration of chlorophyll in plants decrease with infection of pathogen (Akbar et al, 2023 ; Smith et al, 2023 ; Sobhy et al, 2023 ). The decreased chlorophyll content in leaves following fungal invasion may be attributed to the excessive loss of water owing to increased stomatal conductance (Baghbani et al, 2019 ) or to the overproduction of ROS as a protective barrier which further accelerate the breakdown of chlorophyll.…”
Section: Discussionmentioning
confidence: 99%